'When you are a data collector you must expect anything'. Barriers, boundaries and breakthroughs: insights from the South African data-collection experience. (June 2020) - Roberts, Kathryn; Gordon, Sarah; Sherr, Lorraine; Stewart, Jackie; Skeen, Sarah; Macedo, Ana; Tomlinson, Mark
The impact of the research process on the researcher is an emerging topic of interest. Data collection in most low- and middle-income countries (LMICs) is often the responsibility of community members who are identified and trained specifically for data collection. When research involves data on mental health and social well-being, data collectors may have specific competency needs and the task of data gathering may impact data collectors. This study aims to explore the experiences and needs of data collectors within South Africa using qualitative methods to examine the impact of data collection on data collectors. Nineteen data collectors, involved in face-to-face data collection, completed semi-structured interviews exploring their insights, attitudes and experiences. Thematic analysis revealed barriers and challenges associated with research, complexities regarding boundaries within the participant-data collector relationship and the benefits of being involved with research for the individual and the community. Numerous challenges and opportunities are outlined. Findings expose the beneficial and often overlooked contribution of data collectors and warrants key considerations in the planning and implementation of future research to ensure adequate support and standardization of practice.